(untitled) (Journal of the College of Education for Women, 2019)
important dements whichtheconsideredHeadings and titles areThe Leads to pay attention the reader when he reads a newspaper Because it gives for a reader a summary about significant events and journalism arts which published in a page such as (news، reportage،journalism conversations and interview). On the other hand، all design pros ramming produce new tools in the art of direct and adds all the lends، size، shapes،colours،letters، margins between lines in accurate way in order to pay attention for the reader . The first chapter is focused on the research problem which represented to know the art direct of journalism head line in the first page of Al – Sabah newspaper and the range of advantages of using new techniques and modern programming design through different types of colours، shapes، letters which used in the researcher used an interview as a scientific tool . In the second chapter is focused on development and enhancement the journalism art and concentrate on the concepts and different types of titles in news paper moreover،using and write the journalism title and a design program. In the third chapter is focused on the analysis study of sample in Al- Sabah newspaper from( 1\1\2012- 31\1\2012). Suggestion and Recommendations1-It is a necessary to make a balance in the headlines by using different types of colours،shapes and sizes such as machete. 2-lt is used different colours in writing the headlines by using black colour or red colour in writing a manchete . 3- lt is very necessary to depend on the one kind of letter in writing such as orient form . 4- lt isvery important to use different size in first page of Newspaper a according to important event and published subjects . Finally، it is very necessary to know and read the foreign news and Arabic news in order to know the desire of reader and style ofnews paper .